Do We Need a Fresh Quest for the Historical Jesus? - Lifu Liu (Studies in Social Science & Humanities, 2023)
Jesus Christ has significantly influenced religion through his teachings. Historical Jesus research has been conducted through four periods: Old Quest, Intermittent Period, New Period, and Third Period. The Third Quest, a historical Jesus study, integrates multiple disciplines to illuminate Jesus’ context, addressing issues like overemphasis on irrelevant information and undervaluing relevant data. It has expanded historical Jesus studies with a more nuanced understanding of Jesus’ life and teachings. Feminism plays a very important role in Third Quest. By studying the roles played by women in historical Jesus, we can explore Jesus’ stance on women’s liberation; This cannot be ignored.